PENGARUH MEDIA EXPOSURE, SENSITIVITAS INDUSTRI, DAN GROWTH TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Martin Marcelino Purnomo (Parsimonia - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of media exposure, industrial sensitivity, and growth on the disclosure of corporate social responsibility in all companies listed on the Indonesia Stock Exchange for the period 2017 to 2019. The sample of this study is all publicly traded companies listed on the Stock Exchange. Indonesia for the 2017-2019 period with a total of 95 companies. This study uses multiple regression analysis to test the effect of each variable. The results of this study indicate that media exposure and industrial sensitivity have a positive effect on CSR disclosure. Meanwhile, in this study, growth shows that growth does not affect CSR disclosure. In the theory of legitimacy, it provides an illustration of the difference between the values ​​adopted by the company and the values ​​of the community, so the company will be in a threatened position or a legitimacy gap, in that the company will try to minimize the legitimacy gap with CSR disclosure. So that the disclosure of CSR will be a positive signal that can reduce information asymmetry.